More direct evidence for early dispersal of bread wheat to the eastern Chinese coast ca. 2460–2210 BC - Chen, Xuexiang; Yu, Shi-Yong; Wang, Qingzhu; Cui, Xiaoxi; Underhill, Anne P. (Archaeological and anthropological sciences, 2020)
Originally domesticated in southwestern Asia, bread wheat represents an exotic element that eventually broadened the subsistence strategies in more than one area of China. Notwithstanding a growing body of data, its timing, pace, and pathway of dispersal as well as social impact in China continue to be debated. Here, we present one more line of direct evidence for early occurrence of bread wheat at the coastal site of Sujiacun in the Rizhao area of southeastern Shandong Province, China. Our results by direct dating of a mixed crop cohort consistently show that bread wheat was first introduced into the eastern Chinese coast about 2460–2210 BC. The directly dated wheat grain at Sujiacun is coeval with those found at the Zhaojiazhuang site. Our finding implies that there may have been more than one possible route for wheat transmission to China, including the Eurasian Steppe route. Given the coastal location of the two Shandong sites yielding early wheat remains, however, a trans-Asian dispersal including ocean travel cannot be excluded. Comparison with existing data suggests that, upon arrival on the coast of eastern Shandong, bread wheat quickly dispersed inland and arrived in the Central China Plain and North China Plain by about 2000 BC. It appears that bread wheat was not cultivated extensively in Shandong until hundreds of years later, perhaps due to limitations of climatic, technological, and/or social factors.